2005
DOI: 10.1176/appi.ajp.162.9.1588
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Depression in Old Age Compared to Middle Age: A Systematic Review of Comparative Studies

Abstract: With control for confounding variables, remission rates of depression in patients in late life are little different from those in midlife, but relapse rates appear higher. Findings underline the importance of assessing factors related to patient age and not just to age itself in evaluations of risk factors for poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
1
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(174 citation statements)
references
References 76 publications
(80 reference statements)
3
149
1
12
Order By: Relevance
“…22 Successful diagnosis and treatment of LLD improves depressive symptoms and decreases suicide rates. 23 Despite the demonstrated effectiveness of treatment, many obstacles remain.…”
Section: Late-life Depression: Definition Extent Burden and Hopementioning
confidence: 99%
“…22 Successful diagnosis and treatment of LLD improves depressive symptoms and decreases suicide rates. 23 Despite the demonstrated effectiveness of treatment, many obstacles remain.…”
Section: Late-life Depression: Definition Extent Burden and Hopementioning
confidence: 99%
“…Once recovered from depressive symptoms, older people have a high risk of recurrence, with rates ranging between 15 and 50% (Hinrichsen and Hernandez, 1993;Little et al, 1996;Flint and Rifat, 1997;Kivela et al, 2000;Beekman et al, 2002). Recent studies revealed that older depressives have a higher risk of recurrence after recovery compared to younger adults (Mueller et al, 2004;Mitchell and Subramaniam, 2005). These prognosis data demonstrate the need to identify characteristics of older persons who are at high risk for recurrence.…”
Section: Introductionmentioning
confidence: 97%
“…The long-term prognosis for depression in later life has generally been considered mixed with only one quarter to one third of the patients robustly well at 1-3 years of follow-up (Murphy, 1983;Post et al, 1992;Cole et al, 1999;Beekman et al, 2002; for a review see Mitchell and Subramaniam, 2005). Once recovered from depressive symptoms, older people have a high risk of recurrence, with rates ranging between 15 and 50% (Hinrichsen and Hernandez, 1993;Little et al, 1996;Flint and Rifat, 1997;Kivela et al, 2000;Beekman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While these psychotherapies have been shown to be effective in the treatment of LLD, as with medication treatments, a significant portion of individuals receiving treatment do not respond to these interventions (14, 23). Given the cognitive demands of psychotherapy and known associations between cognitive deficits and cortical atrophy in older adults (25, 26), as well as the impact of cortical atrophy on antidepressant treatment response (18, 27), there is compelling evidence to suggest that cortical atrophy may have a deleterious impact on psychotherapy treatment outcomes. Further, given recent findings of prominent reductions in right hemisphere cortical thickness associated with familial risk of depression; indices of cortical thickness may be a particularly sensitive phenotypic marker of psychotherapy treatment response in older adults.…”
Section: Introductionmentioning
confidence: 99%